Advantages of nonlinear energy harvesting with dielectric elastomers. (3rd March 2019) - Thomson, G.; Lai, Z.; Val, D.V.; Yurchenko, D.
Abstract: The paper considers electrostatic energy conversion from ambient vibrations using dielectric elastomers. A novel device for vibration energy harvesting is proposed, studied and compared with a vibroimpact device previously investigated by the authors for the same purpose. The nonlinear dynamic behaviour of the new device is explored numerically and the results presented indicate excellent energy harvesting capabilities with an energy density of 9.15 J∕kg. The proposed device particularly benefits from stiffness nonlinearity of its dielectric membranes as is demonstrated by comparison with their linear behaviour. The influence of nonlinearity is further investigated, with results compared against recent reports on dielectric elastomer energy harvesting and other forms of vibration energy harvesting. Two electrical schemes that can be used for the electrostatic energy conversion are also introduced and compared in terms of their suitability for the proposed device.